Teorema de Riemann-Roch e aplicações - Arruda, Rafael Lucas de [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
O objetivo principal deste trabalho é estudar o Teorema de Riemann-Roch, um dos resultados fundamentais na teoria de curvas algébricas, e apresentar algumas de suas aplicações. Este teorema é uma importante ferramenta para a classificação das curvas algébricas, pois relaciona propriedades algébricas e topológicas. Daremos uma descrição das curvas algébricas de gênero g, 1≤ g ≤ 5, e faremos um breve estudo dos pontos de inflexão de um sistema linear sobre uma curva algébrica

The main purpose of this work is to discuss The Riemann-Roch Theorem, wich is one of the most important results of the theory algebraic curves, and to present some applications. This theorem is an important tool of the classification of algebraic curves, sinces relates algebraic and topological properties. We will describle the algebraic curves of genus g, 1≤ g ≤ 5, and also study inflection points of a linear system on an algebraic curve
Keywords: Geometria algebrica; Curvas algebricas; Riemann-Roch, Teoremas de; Riemann, Superficies de; Riemann surfaces; Algebraic curves; Divisors; Linear system; Riemann-Roch theorem; Classification of algebraic curves; Inflection points; Weierstrass points